PERANCANGAN AWAL PABRIK BIOHIDROGEN DARI LIMBAH CAIR PABRIK KELAPA SAWIT DENGAN FERMENTASI ANAEROBIK PADA KONDISI TERMOFILIK - Bambang Trisakti, Irvan, Hari Tiarasti, Irma Suraya (Universitas Sumatera Utara, 2012)
Indonesia has a lot of natural resources which is deficient to fulfill the energy demand of consumers, particularly fuel. Therefore, the government keeps on promoting the search for alternative energy. One of these is hydrogen. Hydrogen is an environmental friendly product that does not produce carbon emissions. In the formation of hydrogen we can use carbohydrate-rich waste as a raw material and by using fermentation process. However, it is still limited research only. So this encourage us to design biohydrogen plant from palm oil mill effluent (POME) with the conditions of thermophilic anaerobic fermentation in order to accomplish the needs of consumers and contribute in developing clean technologies. For the production capacity of 495.1694 tons / year, the total investment required to build a factory of biohydrogen in Indonesia is Rp. 507,190,573,523, - with a total production cost of Rp. 354,636,600,139, -. Parameter feasibility of the production capacity of 495.1694 tons / year is the total product sales of Rp 174,261,989.701, - and net income 180,030,185,327, -. Profit Margin (PM) 41.9% Break Even Point (BEP) 45.24%, Return on Investment (ROI) 35.5%, Pay Out Time (POT) 2.82 years, Return of Network (RON) 59.16%, Internal Rate of Return (IRR) 53.52 %.Keywords: anaerobic fermentation, biohydrogen, IRR, POME, thermophilic